East African Agriculture and Climate Change - Waithaka, Michael; Nelson, Gerald C.; Thomas, Timothy S.; Kyotalimye, Miriam (International Food Policy Research Institute, 2013)
Agriculture accounts for 43 percent of the surveyed nations’ annual gross domestic product (GDP), on average, although the precise proportions vary considerably from country to country. For example, agriculture in Burundi, DRC, Ethiopia, Sudan, and Tanzania accounts for more than 50 percent of GDP while in Eritrea, Kenya, and Madagascar it accounts for less than 30 percent. Kenya’s low percentage is due to structural transformation toward a less agriculture-based economy. Despite these differences, farming in all the surveyed nations is dominated by smallholders reliant on rainfall. These farmers face the challenges of land degradation, poor soil fertility management, and continuous cropping. Sluggish growth in agricultural productivity translates into slow overall growth and generally low per capita income levels. Meanwhile, population growth in these 10 East African countries is among the highest in the world, which threatens to worsen already severe food insecurity.